Investigation of voice characteristics in special educators using Dysphonia Severity Index (DSI) - K, Yeshoda; R, Rajasudhakar; T, Jayakumar; G, Amoolya; Damodaran, Deepthi (Journal of All India Institute of Speech and Hearing, 2013)
Special educators are those who educate children with special needs. They are involved in vocally demanding profession; especially those who deals children with Hearing Impairment and Mental retardation. It is likely that they are vulnerable to develop voice problems in due course. Not many studies have been done to investigate the voice characteristics of special educators working in preschool set up. The objective of the present study was to investigate the voice characteristics of special educators working in preschool, using objective vocal quality measurement (Dysphonia Severity Index, DSI). It is also focused on studying the effect of number of teaching years on DSI. Eighteen special educators who educate special children were included in the study. Among them, thirteen were females and five were males were included in the study. Female participants were further sub grouped based on number of years of teaching experience. Group 1 included teachers having less than 8 years of teaching experience and Group 2 included teachers having more than 8 years of teaching experience. lingWAVES version 2.5 (WEVOSYS German) was used to calculate DSI. The parameters extracted for the calculation of DSI were lowest intensity, highest frequency, maximum phonation time and jitter. Mann-Whitney U test was used to find the effect of gender and number of teaching years. The values of DSI parameters of special educators were within normal limits when compared with non professional voice users except for the highest frequency in female participants. There was no significant difference found between the DSI values of males and females. Years of teaching experience did not have any effect on the parameters of DSI. Teaching children with special needs did not have any effect on the most of the DSI parameters for the special educators in the present study. Further researches on larger sample would yield insight about the voice quality of preschool special educators.